2016
DOI: 10.1088/1361-648x/29/6/064001
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of K-doped picene film on HOPG

Abstract: We have performed potassium (K)-doping dependent photoemission (PES) measurements of picene film on highly oriented pyrolytic graphite (HOPG). K-doping dependent valence band PES data exhibits a shift of the valence band to a higher binding energy, indicative of the charge transfer from the K atoms to the picene film. K-doping dependent PES spectra near the Fermi level (E ) show the appearance and disappearance of a Fermi edge, indicating the metallic properties of the film at certain K concentrations. High-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recently, doping of metal atoms, especially alkali metal atoms, into polycyclic aromatic hydrocarbon (PAH) materials attracts much attention because of the appearance of superconductivity. , As a typical PAH molecule, picene has an armchair aromatic molecular configuration composed of five benzene rings. This molecule has been demonstrated to be superconducting upon potassium (K) or rubidium doping. , The superconducting transition temperature could be as high as 18 K. ,, However, because of the very low shielding fraction (<1.2%) and lack of repeatability, the superconductivity in such a system is questioned by Tanigaki and co-workers, Knupfer and co-workers, and Ruff et al Extensive efforts have been devoted to settle this debate. ,,,,, ,, Combining photoemission spectroscopy (PES) experiments and density functional theory plus dynamical mean-field theory (DFT+DMFT) calculation, Ruff et al found that K x Picene was a correlated Mott insulator for x = 1, 2, 3 . Yokoya and co-workers performed the PES studies on the electronic structure shift of K-doped picene film on highly oriented pyrolytic graphite (HOPG) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, doping of metal atoms, especially alkali metal atoms, into polycyclic aromatic hydrocarbon (PAH) materials attracts much attention because of the appearance of superconductivity. , As a typical PAH molecule, picene has an armchair aromatic molecular configuration composed of five benzene rings. This molecule has been demonstrated to be superconducting upon potassium (K) or rubidium doping. , The superconducting transition temperature could be as high as 18 K. ,, However, because of the very low shielding fraction (<1.2%) and lack of repeatability, the superconductivity in such a system is questioned by Tanigaki and co-workers, Knupfer and co-workers, and Ruff et al Extensive efforts have been devoted to settle this debate. ,,,,, ,, Combining photoemission spectroscopy (PES) experiments and density functional theory plus dynamical mean-field theory (DFT+DMFT) calculation, Ruff et al found that K x Picene was a correlated Mott insulator for x = 1, 2, 3 . Yokoya and co-workers performed the PES studies on the electronic structure shift of K-doped picene film on highly oriented pyrolytic graphite (HOPG) .…”
Section: Introductionmentioning
confidence: 99%
“…This molecule has been demonstrated to be superconducting upon potassium (K) or rubidium doping. , The superconducting transition temperature could be as high as 18 K. ,, However, because of the very low shielding fraction (<1.2%) and lack of repeatability, the superconductivity in such a system is questioned by Tanigaki and co-workers, Knupfer and co-workers, and Ruff et al Extensive efforts have been devoted to settle this debate. ,,,,, ,, Combining photoemission spectroscopy (PES) experiments and density functional theory plus dynamical mean-field theory (DFT+DMFT) calculation, Ruff et al found that K x Picene was a correlated Mott insulator for x = 1, 2, 3 . Yokoya and co-workers performed the PES studies on the electronic structure shift of K-doped picene film on highly oriented pyrolytic graphite (HOPG) . Though the metallic behavior was revealed at a certain K-doping level, a superconducting gap was not observed at 4 K .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for picene monolayers on Au(111) a dimerization of the two molecules in the unit cell has been suggested . Another consequence of the zigzag shape of picene are the pseudo‐degenerated two lowest unoccupied molecular orbitals (LUMOs) and the likewise energetically closely spaced highest occupied molecular orbital (HOMO) and HOMO‐1, which is believed to be the key to the superconductivity with exceptionally high critical temperature of K‐doped picene . In order to show the impact of molecular shape and to correlate structure and electronic structure at organic‐metal interfaces, we measured low energy electron diffraction (LEED) and angle resolved ultraviolet photoelectron spectroscopy (ARUPS) of vacuum‐sublimed picene on Ag(111), Ag(110), Cu(111), and Cu(110) and compare our results with literature of pentacene on the same surfaces .…”
Section: Introductionmentioning
confidence: 99%